AUDITORY–MOTOR THINKING AS AN INTENTIONAL STRUCTURE OF MUSICAL PERFORMANCE: PHENOMENOLOGICAL AND SEMIOTIC DIMENSIONS - ZAIETS Vitalіi; ZAIETS, Oksana; BENZIUK, Oleksandr; ZAIETS, Yuliia (Studia Universitatis Babes-Bolyai Musica, 2026)
The article substantiates the concept of auditory–motor thinking as a key artistic–cognitive structure of musical performance. Drawing on the phenomenological tradition of analyzing embodied consciousness and the temporality of musical action, it proposes a distinction between sensorimotor integration as the physiological precondition of performance and auditory–motor thinking as an intentionally organized process of shaping artistic meaning. It is demonstrated that musical performance cannot be reduced to the coordination of auditory and motor responses; rather, it emerges as an integral act of performative consciousness in which auditory projection, motor structuring, and expressive regulation are unified within a single temporal perspective.